Implementation of Fuzzy Logic in the Monitoring and Controlling System for Temperature and pH of Fry Aquarium Water Betta Fish Based on the Internet of Things - Wahyudi, Rico; Ullah, Aulia; Zarory, Hilman; Faizal, Ahmad (PROtek : Jurnal Ilmiah Teknik Elektro, 2025)
A problem faced by betta fish farmers is the difficulty in monitoring and controlling the temperature and pH of the water in betta fish fry ponds. This condition causes many deaths of Betta fish fry which results in a reduction in the supply of Betta fish seeds. To overcome this problem, a system based on the Internet of Things was developed(IoT) which can monitor in real time and control the temperature and pH of the water in the Betta fish fry pond. This system is implemented in an aquarium equipped with artificial intelligence in decision making which aims to keep the temperature and pH of the aquarium water stable. The components used in this system include ESP32, DS18B20 temperature sensor, water pH sensor, Thermo Electric Cooler (TEC), heater, DC pump, and fuzzy logic implementation. The results of system testing for 14 days showed that the system was able to monitor and control the temperature and pH of the aquarium water, maintaining ideal conditions for Betta fish fry with an average temperature of 28.79°C and an average water pH of 7.45. The system also succeeded in reducing the mortality rate of Betta fish fry, as proven in comparative tests between aquariums without system implementation and aquariums with system implementation. In this trial, each aquarium was filled with 30 betta fish fry. The results showed that the aquarium with system implementation was able to reduce the death rate of Betta fish fry by 5 or 16.67% from a total of 30 fish. Meanwhile, aquariums without system implementation had a death rate of 12 betta fish fry or 40% of the total of 30 betta fish fry.